Innovations for potential entrepreneurs in service quality and customer loyalty in the hospitality industry. Issue 3 (18th December 2020) - Satti, Zoya Wajid; Babar, Samreen Fahim; Parveen, Shagufta; Abrar, Kashif; Shabbir, Asma
Abstract : Purpose: This study aims to investigate the role of moderated mediation between innovation in service quality and customer loyalty in the hospitality industry for potential entrepreneurs in the hospitality industry. Design/methodology/approach: The authors have collected data from customers of the hospitality industry of significant cities of Pakistan using 362 structured questionnaires. Structural equation modelling was used to find out moderated mediation between innovation in service quality and customer loyalty in the hospitality industry for potential entrepreneurs in the hospitality industry. Findings: The results showed that the role of customer satisfaction as a mediator and the role of perceived price fairness as a moderator between service quality and customer loyalty is statistically significant. Customers are influenced by price, and it leads to their satisfaction in the hospitality industry. Research limitations/implications: The results of this study can be used by managers of the restaurant industry to enhance customer loyalty by focusing on customer satisfaction and perceived price. Originality/value: The evidence documented in this paper is first known to measure the role of a mediator and moderator between service quality and customer loyalty for potential entrepreneurs. This paper will add to the literature of service quality in the hospitality industry concerning the role of customer satisfaction and perceived price fairness for future and potential entrepreneurs.